Sandfly fauna in an area endemic for visceral leishmaniasis in Aracaju, State of Sergipe, Northeast Brazil - Sierpe Jeraldo, Veronica de Lourdes; de Oliveira Goes, Marco Aurelio; Casanova, Claudio; deMelo, Claudia Moura; de Araujo, Edilson Divino; Brandao, Sinval Pinto; Rocha Cruz, Danilo Esdras; Pinto, Mara Cristina [UNESP] (Soc Brasileira Medicina Tropical, 2012)
Introduction: In recent years, visceral leishmaniasis, a major public health problem, has been spreading from the rural to urban areas in many areas of Brazil, including Aracaju, the capital of the State of Sergipe. However, there are no studies of the sandfly fauna in this municipality or its variation over the year. Methods: Phlebotomine sandflies were collected from a rural area of Aracaju from September 2007 to July 2009. Modified CDC ultra-violet (UV) light traps were used to evaluate sandfly monthly distribution and their presence in the domestic and peridomestic environments. Results: The most abundant species was Lutzomyia longipalpis (90.4%) followed by Evandromyia lenti (9.6%). A chicken shed trap site had the highest proportion of L. longipalpis (51.1%) and large numbers of L. longipalpis were also collected in the houses closest to the chicken shed. There was a positive correlation between monthly rainfall and L. longipalpis abundance. Conclusions: Lutzomyia longipalpis is the most abundant species and is probably the main vector of the visceral leishmaniasis agent in the rural area of Aracaju. An increase in L. longipalpis frequency was observed during the rainy season. The peridomicile-intradomicile observations corroborate the importance of chicken sheds for the presence of L. longipalpis in the peridomestic environment. The great numbers of L. longipalpis inside the houses confirm the endophilic behaviour of this species and the possibility of visceral transmission in the intradomicile.

INTRODUÇÃO: Nos últimos anos, a leishmaniose visceral, um importante problema de saúde pública, vem apresentando expansão das áreas rurais para as urbanas de muitas regiões do Brasil, incluindo-se Aracaju, capital do Estado de Sergipe. No entanto, não existem estudos sobre a fauna de flebotomíneos presente nesse município ou de sua distribuição ao longo do ano. MÉTODOS: As coletas de flebotomíneos foram realizadas em uma área rural de Aracaju, capital do Estado de Sergipe no periodo de setembro de 2007 a julho de 2009. Armadilhas CDC modificadas acopladas com luz ultravioleta (UV) foram utilizadas para avaliar a distribuição mensal e a presença de flebotomíneos nos ambientes doméstico e peridoméstico. RESULTADOS: Lutzomyia longipalpis foi a espécie mais abundante (90,4%), seguida por Evandromyia lenti (9,6%). Os locais com as maiores quantidades de L. longipalpis (51,1%) foram um galinheiro e as casas mais próximas a ele. Houve uma correlação positiva entre a precipitação mensal e a abundância de L. longipalpis. CONCLUSÕES: Lutzomyia longipalpis é a espécie mais abundante e, provavelmente, o principal vetor do agente da leishmaniose visceral na área rural de Aracaju. Foi observado um aumento na frequência de L. longipalpis nos meses chuvosos. As coletas realizadas no ambiente externo e interno dos domicílios reforçam a relevância dos galinheiros para a presença de L. longipalpis no ambiente peridoméstico. O grande número de L. longipalpis dentro das casas confirma o comportamento endofílico dessa espécie e a possibilidade de transmissão intradomiciliar da leishmaniose visceral.
Fauna flebotomínica em área endêmica de leishmaniose visceral em Aracaju, Estado de Sergipe, Nordeste do Brasil
Keywords: Phlebotominae; Sandfly; Lutzomyia; Sergipe